Arabidopsis SDG8 Potentiates the Sustainable Transcriptional Induction of the Pathogenesis-Related Genes PR1 and PR2 During Plant Defense Response - Zhang, Xue; Ménard, Rozenn; Li, Ying; Coruzzi, Gloria M.; Heitz, Thierry; Shen, Wen-Hui; Berr, Alexandre (Frontiers in Plant Science, 2020)
Post-translational covalent modifications of histones play important roles in modulating chromatin structure and are involved in the control of multiple developmental processes in plants. Here we provide insight into the contribution of the histone lysine methyltransferase SET DOMAIN GROUP 8 (SDG8), implicated in histone H3 lysine 36 trimethylation (H3K36me3), in connection with RNA polymerase II (RNAPII) to enhance Arabidopsis immunity. We showed that even if the sdg8-1 loss-of-function mutant, defective in H3K36 methylation, displayed a higher sensitivity to different strains of the bacterial pathogen Pseudomonas syringae, Effector-triggered immunity (ETI) still operated, but less efficiently than in the wild-type (WT) plants. In sdg8-1, the level of the plant defense hormone salicylic acid (SA) was abnormally high under resting conditions and was accumulated similarly to WT at the early stage of pathogen infection but quickly dropped down at later stages. Concomitantly, the transcription of several defense-related genes along the SA signaling pathway was inefficiently induced in the mutant. Remarkably, albeit the defense genes PATHOGENESIS-RELATED1 (PR1) and PR2 have retained responsiveness to exogenous SA, their inductions fade more rapidly in sdg8-1 than in WT. At chromatin, while global levels of histone methylations were found to be stable, local increases of H3K4 and H3K36 methylations as well as RNAPII loading were observed at some defense genes following SA-treatments in WT. In sdg8-1, the H3K36me3 increase was largely attenuated and also the increases of H3K4me3 and RNAPII were frequently compromised. Lastly, we demonstrated that SDG8 could physically interact with the RNAPII C-terminal Domain, providing a possible link between RNAPII loading and H3K36me3 deposition. Collectively, our results indicate that SDG8, through its histone methyltransferase activity and its physical coupling with RNAPII, participates in the strong transcriptional induction of some defense-related genes, in particular PR1 and PR2, to potentiate sustainable immunity during plant defense response to bacterial pathogen.